Totally Extraperitoneal Repair in Inguinal Hernia: More Than a Decade's Experience at a Tertiary Care Hospital. Issue 4 (August 2019) - Krishna, Asuri; Bansal, Virinder K.; Misra, Mahesh C.; Prajapati, Omprakash; Kumar, Subodh
Abstract : Introduction: There are 2 standard techniques of laparoscopic groin hernia repair, totally extraperitoneal repair (TEP) and transabdominal preperitoneal repair (TAPP). TEP has the advantage that the peritoneal cavity is not breached but is, however, considered to be more difficult to master when compared with TAPP. We describe herein our experience of TEP repair of inguinal hernia over the last 14 years. Materials and Methods: This study is a retrospective analysis of a prospectively maintained database of all patients with groin hernia who underwent TEP repair in a single surgical unit between January 2004 and January 2018. Patients' demographic profile and hernia characteristics (duration, side, extent, content, and reducibility) were noted in the prestructured proforma. Clinical outcomes included the operation time, intraoperative and postoperative complications, length of postoperative hospital stay, hernia recurrence, chronic pain, recurrence, seroma, and wound infections. Long-term follow-up was carried out in the outpatient department. Results: Over the last 14 years, TEP repair was performed in 841 patients and a total of 1249 hernias were repaired. The mean age of patients was 50.7 years. There were 748 primary and 345 unilateral hernias. The majority were direct (61%) inguinal hernias. Telescopic dissection was the commonest method of space creation. The average operating time was 54.8 and 77.9 minutes for unilateral and bilateral hernias, respectively. With 81 conversions, the success rate for TEP was 93.5%. Seroma was the most common postoperative complication seen in 81 patients. The incidence of chronic groin pain was 1.4%. The follow-up ranged from 3 months to 10 years, and there were only 3 recurrences (<1%). Conclusion: In conclusion, TEP repair is an excellent technique of laparoscopic inguinal hernia repair with acceptable complications after long-term follow-up.